Os países em desenvolvimento e os mecanismos de solução de controvérsias no comércio internacional - Cavalhero, Lirian Sousa Soares (2006)
With the development of the international trade, the quarrels became constant around the forms of regulation and the solution of conflicts between the nations, in this context appears the World Trade Organization (WTO). Before entering the study of the OMC and of its methods of solution of conflicts, it is necessary investigate the history of the development of the international trade before and after the Second World War I, and the multilateral organisms with emphasis in the General Agreement of Commerce and Tariffs (GATT). The ways of solution of international conflicts are object of the study, as much its historical part, as the current one, having as main focus the Dispute Settlement Body (DSB) of the WTO. As much in the historical part as in the part of the methods of international solution of conflicts, the participation of the developing countries is studied. And, is made studies of cases of the performance of the developing countries in some demands proposal before the DSB. Of this form, the work demonstrated as it was the participation of the developing countries in the development of the international trade and in the DSB of WTO